Development of formulations based on Streptomyces rochei strain PTL2 spores for biocontrol of Rhizoctonia solani damping-off of tomato seedlings. Issue 6 (3rd June 2017) - Zamoum, Miyada; Goudjal, Yacine; Sabaou, Nasserdine; Mathieu, Florence; Zitouni, Abdelghani
ABSTRACT: Rhizoctonia solani is one of the most problematic soil-borne pathogenic fungi for several crop cultures worldwide. This study highlights the effectiveness of high-antagonistic Streptomyces rochei strain PTL2, isolated from root tissues of Panicum turgidum, in controlling the R . solani damping-off and growth promotion of tomato (cv. Marmande) seedlings. The isolate PTL2 was characterised for in vitro biocontrol and plant growth-promoting traits. It exhibited remarkable positive results in all trials, including production of hydrogen cyanide, siderophores, 1-aminocyclopropane-1-carboxylate deaminase and phytohormones, chitinolytic activity and inorganic phosphate solubilisation. PTL2 spores were formulated as wettable talcum powder, sodium alginate pellets and sodium alginate-clay pellets. Their abilities in the biocontrol of R . solani and plant growth promotion were investigated in autoclaved and non-autoclaved soils. Talcum powder and sodium alginate pellets significantly reduced the damping-off severity index compared to a positive control. The talcum powder exhibited the highest protective activity, reducing the disease incidence from 89.3% to 14.1%, whereas chemical seed treatment with Thiram ® provided a disease incidence of 16.7%. Furthermore, the talc-based powder formulation resulted in greatest increases in the root length, shoot length and dry weight of seedlings. The interesting biocontrol potential and growth enhancement of tomato seedlings open up promising perspectives for the possible application of talcum powder formulation based on PTL2 spores in crop improvement.